The Power Of Muslim Influencers On Purchase Intention Toward Wardah Cosmetics - Idaman, Northa; Iqbal Fasa, Muhammad; Lusia Putri, Siska (Journal of Halal Research, Policy, and Industry, 2025)
This study investigates the influence of Muslim influencer characteristics trustworthiness, familiarity, and expertise—on purchase intention toward Wardah cosmetic products on social media. Wardah, as a halalcertified cosmetic brand, relies heavily on influencer marketing to reach its target market of Muslim consumers. Using a quantitative research design, data were collected through an online questionnaire distributed to 150 purposively selected respondents who follow Muslim beauty influencers and are familiar with the Wardah brand. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all three variables trustworthiness, familiarity, and expertise have a positive and significant effect on purchase intention. Among them, trustworthiness shows the strongest influence, highlighting the importance of perceived honesty and ethical alignment between the influencer and their audience. This study contributes to the literature on influencer marketing in the halal cosmetics sector and provides practical insights for brands aiming to build effective partnerships with Muslim influencers. Selecting influencers who are not only popular but also credible, familiar, and expert in their field is crucial for shaping consumer trust and driving purchase behavior in religiously conscious markets.